The Saz as a Mode of Understanding Alevism - Muradoglu, Iris Sibel (Voices: A World Forum for Music Therapy, 2017)
An attempt to give insight into who Alevis are and what Alevism is, only further demonstrates the complexities that arise in doing so. However, this ambiguity is essential to discuss in terms of what this paper seeks to answer and that is: How can we comprehend the complexities of Alevism, using music and the saz as a mode of understanding that does not further reduce them to just representations of folklore? For those who identify as Alevis, music, and in particular the saz, play a central role in this formation of identity. Alevis in their religious rituals use music and dance, and thus their practices oppose that of a Sunni-majority Turkey. In this sense, when it comes to incorporating music in their religious traditions, the Turkish state undermines and therefore considers them illegitimate religious practices and deems them purely as cultural ones. Emphasizing the importance of the saz aims to bridge the cultural and religious implications of the instrument and thus metaphorically serve as also a bridge in understanding the complexities of defining Alevis. Contextualizing is imperative for understanding the performative piece at the end of the paper. This section aims to provoke the reader to think about what they have just read and listen to a piece composed by an Alevi saz player who was victim to one of the atrocities in Alevi history. The video is supplemented by the voices of my research participants who share their thoughts about the song—“Güle Yel Değdi”(Rose is Touched by the Breeze), the composer of the song—Hasret Gültekin, and about Alevism in general.